MENGATASI GANGGUAN PERKEMBANGAN BAHASA (DELAY ON READING) PADA ANAK SD KELAS RENDAH MELALUI PENDEKATAN PENGALAMAN BAHASA DAN METODE FONIK - Dwi Puspita, Ryan (STKIP Subang, 2015)
Problems faced by children are usually associated with a disruption in the child's development. If not addressed, it will continue in the disruption next development phase is the development phase of school children. (Sri Maryati Deliana, et al, p. 1). One of them is a developmental disorder of language. Language serves as a communication tool and an important tool in the child's life. Through language, the child can interact, share experiences, and can improve the intellectual, namely in order to develop the knowledge and language skills. For children it is a period of development that must be nurtured and developed so that they can take advantage of language skills to the fullest. Without the guidance and direction feared their language development is not as expected by the parents at home and by teachers at school. (Dr. Enny Zubaidah, M. Pd., P. 1). Language delays are common disorders in early childhood or in the lower grade elementary school children. Language disorders such as this will hinder the social development of children. In this paper the child language disorders focused on the problem of type receptive language disorder. Examples of receptive language disorders in this case is the delay reading, children recognize letters but when united in one word the child can not memaknainya.Seperti other examples. As another example, a child who just saw the house, can not say that it is a home for disturbed memory warehouse. Also the ability to deliver the order (the ability to recognize or reproduce symbols in a sequence as presented) disturbed. For example, after introduced the symbol numbers 1 to 10 in a row, the child can not be mentioned in the order.